Barriers to acceptance of information and communication technology in agricultural extension in Indonesia. (September 2019) - Purnomo, Sutrisno Hadi; Kusnandar,
The use of information and communication technology (ICT) has become progressively widespread in various sectors including agriculture. This study investigated the barriers to the diffusion of ICT in agricultural extension. Further, the study examined the effect of barriers toward ICT acceptance in agricultural extension. A paper and pencil survey by mail was conducted to collect data from 355 respondents in the Greater Surakarta Region, Indonesia. The study discovered that individual barriers, cultural barriers, government policy barriers, support and technological barriers significantly influenced the acceptance of ICT. In line with the Technology Acceptance Model (TAM), these variables influenced perceived ease of use, perceived usefulness and perceived intention to use of ICT. The findings suggested the methods that could be adopted by governments and non-government bodies to overcome the barriers in ICT implementation.